(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
Semantic groups of astronomic metaphor terms in particular names of phenomena, processes, theories, celestial bodies, time intervals are described. Semantic structure of metaphors are characterized, changes in seme structure of appellations are revealed by means of component analysis technique. Groups of commonly used words functioning as metaphor appellations in astronomy are described. The main functions of astronomic metaphor terms are ascertained.